Relevance of positive surgical margins in localized renal cell carcinoma after surgical resection: predictive factors and survival implications - Egen, Luisa; Quan, Allison; Gottstein, Luise; Haney, Caelán Max; Walach, Margarete; Mühlbauer, Julia; Worst, Thomas; Michel, Maurice Stephan; Kowalewski, Karl-Friedrich (Clinical genitourinary cancer, 2024)
Introduction - The implications of positive surgical margins (PSM) after surgery for renal cell carcinoma (RCC) remain subject of discussion. This study aimed to identify risk factors for PSM, assess its effect on overall survival (OS), and determine predictors of OS. - Patients and Methods - Data from RCC surgeries at Mannheim University Medical Center between 2010 and 2023 was analyzed. Propensity score matching balanced PSM and control groups using age, surgical approach, tumor stage, histological subtype, and American Association of Anesthesiologists (ASA) score. Logistic and cox regression models predict PSM and OS, respectively. Kaplan-Meier analysis compared OS of PSM patients and controls. - Results - A total of 1066 RCC patients were included. Propensity score matching yielded 32 PSM patients and 96 controls. Multivariable logistic regression identified tumor stage ≥ T3a (odds ratio [OR] = 2.74, 95% confidence interval [CI] = 1.0-6.8, P = .04) and chromophobe, compared to clear cell, RCC (OR = 3.19, 95% CI = 1.0-8.7, P = .03) as independent predictors of PSM. Multivariable cox regression found age > 65 years (hazard ratio [HR] = 2.65, 95% CI = 1.7-4.2, P < .01) and tumor stage ≥ T3a (HR = 2.25, 95% CI = 1.4-3.7, P < .01) to predict shorter OS. Partial vs. radical nephrectomy was associated with improved OS (HR = 0.49, 95% CI = 0.3-0.9, P = .02). Kaplan-Meier analysis revealed no OS difference between PSM patients and controls (P = .49) over a 45-month median follow-up. - Conclusion - PSM is not a primary determinant of inferior survival, while age and tumor stage play a more prominent role. A well-calibrated follow-up protocol for PSM patients, combining PSM with coinciding factors such as tumor stage, grade, size, or PSM extent, is crucial for adequate surveillance while preventing excessive interventions.
Online verfügbar: 1. Mai 2024, Artikelversion: 15. Juni 2024
Gesehen am 18.02.2025